RELATIONSHIP BETWEEN UNILATERAL AND BILATERAL COUNTERMOVEMENT JUMP PERFORMANCE AND FORCE-VELOCITY-POWER OUTCOME VARIABLES (Kinesiology, 2023)
The main objective of the present study was to check the relationship between commonly used unilateral and bilateral countermovement jump (CMJ) performance variables (jump heights, unilateral CMJ jump/ bilateral CMJ jump height index, reactive strength index modified and bilateral deficit) and Force-velocity- Power (F-v-P) outcomes from loaded CMJs. Seventeen physical education students performed unilateral CMJ jumps, bilateral CMJ jumps and two-load (20 and 70% of the participant’s body mass) F-v-P tests. The results show that bilateral CMJ jump, unilateral CMJ jump height and the reactive strength index modified calculated from the bilateral CMJ jump are moderately correlated (r = 0.567-0.633, p